Effect analysis of Coulomb damping in shock isolator with different stiffness - Wen Zhaodong; Liu Hongquan; Yan Ming; Zhang Chunhui; Zhanglei (Zhongguo Jianchuan Yanjiu, 2019)
[Objectives] In the passive shock isolator,stiffness and damping are important factors to reduce the transient shock and reduce the vibration transmission. Therefore,it is the key to select the appropriate damping form and consider the appropriate stiffness.[Methods]In this paper,on the basis of established Coulomb damping shock isolation model, the isolation system of Coulomb damping combined with linear spring and switch spring is studied. The system model is expressed by the motion differential equation with the exponential law characteristics to explore the characteristics of Coulomb damping in the shock isolation system and study the stiffness and the law of function on the system response.[Results] The study results show that the Coulomb damping can significantly improve the shock isolation efficiency of the system and reduce the relative displacement amplitude. In the same shock environment,the system composed of Coulomb damping and the switch spring is superior to the linear system in suppressing the peak value and reducing the residual response.[Conclusions]The results of this paper have some guiding significance for the application of Coulomb damping in shock isolation.